A Systematic Review and Meta-analysis on the Impact of Proficiency-based Progression Simulation Training on Performance Outcomes. Issue 2 (22nd August 2021) - Mazzone, Elio; Puliatti, Stefano; Amato, Marco; Bunting, Brendan; Rocco, Bernardo; Montorsi, Francesco; Mottrie, Alexandre; Gallagher, Anthony G.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: To analyze all published prospective, randomized, and blinded clinical studies on the proficiency-based progression (PBP) training using objective performance metrics. Background: The benefit of PBP methodology to learning clinical skills in comparison to conventional training is not settled. Methods: Search of PubMed, Cochrane library's Central, EMBASE, MEDLINE, and Scopus databases, from inception to 1st March 2020. Two independent reviewers extracted the data. The Medical Education Research Study Quality Instrument (MERSQI) was used to assess the methodological quality of included studies. Results were pooled using biased corrected standardized mean difference and ratio-of-means. Summary effects were evaluated using a series of fixed and random effects models. The primary outcome was the number of procedural errors performed comparing PBP and non-PBP-based training pathways. Secondary outcomes were the number of procedural steps completed and the time to complete the task/procedure. Results: From the initial pool of 468 studies, 12 randomized clinical studies with a total of 239 participants were included in the analysis. In comparison to the non-PBP training, ratio-of-means results showed that PBP training reduced the number of performance errors by 60% ( P < 0.001) and procedural time by 15% ( P = 0.003) and increased the number of steps performed by 47% ( P < 0.001). Conclusions and Relevance: Our systematic review and meta-analysis confirms that PBP training in comparison to conventional or quality assured training improved trainees' performances, by decreasing procedural errors and procedural time, while increasing the number of correct steps taken when compared to standard simulation-based training.